Conjugation of insulin onto the sidewalls of single-walled carbon nanotubes through functionalization and diimide-activated amidation - Ng CM (Dove Medical Press, 2016)
Chee Meng Ng,1 Hwei-San Loh,2 Kasturi Muthoosamy,1 Nanthini Sridewi,3 Sivakumar Manickam1 1Manufacturing and Industrial Processes Research Division, Faculty of Engineering, 2Faculty of Science, School of Biosciences, University of Nottingham Malaysia Campus, Semenyih, Selangor, 3Faculty of Science and Defence Technology, National Defence University of Malaysia, Kuala Lumpur, Malaysia Purpose: The high aspect ratio of carbon nanotubes (CNTs) allows the attachment of compounds that enhance the functionality of the drug vehicle. Considering this, use of CNTs as a multifunctional insulin carrier may be an interesting prospect to explore.Materials and methods: The carboxylic acid groups were functionalized on the sidewalls of single-walled CNTs (SWCNTs) followed by diimidation to form amide bonds with the amine groups of the insulin.Results: Scanning transmission electron microscopy and transmission electron microscopy establish clear conjugation of insulin onto the surface of nanotube sidewalls. The incorporation of insulin further increased the solubility of SWCNTs in biological solution for the tested period of 5 months. Bicinchoninic acid assay confirms that 0.42 mg of insulin could be attached to every 1 mg of carboxylated SWCNTs.Conclusion: With the successful conjugation of insulin to SWCNTs, it opens up the potential use of SWCNTs as an insulin carrier which in need of further biological studies.Keywords: diimidation, CNT, SWCNT, increased solubility, carboxylation, drug carrier